Corporate decision-making with macroeconomic uncertainty : performance and risk management - Oxelheim, Lars.; Wihlborg, Clas. (New York ; Oxford : Oxford University Press, 2008)
This book offers the essential elements of a corporate strategy for managing uncertainty in the macroeconomic environment. This strategy enhances firm value by allowing management and external stakeholders to distinguish between changes in the intrinsic competitiveness of the firm and changes in performance caused by macroeconomic fluctuations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Decision making; Uncertainty; Industrial management; Strategic planning; Macroeconomics; Managerial economics; Risk management